2023
DOI: 10.1073/pnas.2300763120
|View full text |Cite
|
Sign up to set email alerts
|

S-lactoyl modification of KEAP1 by a reactive glycolytic metabolite activates NRF2 signaling

Abstract: KEAP1 (Kelch-like ECH-associated protein), a cytoplasmic repressor of the oxidative stress responsive transcription factor Nuclear factor erythroid 2-related factor 2 (NRF2), senses the presence of electrophilic agents by modification of its sensor cysteine residues. In addition to xenobiotics, several reactive metabolites have been shown to covalently modify key cysteines on KEAP1, although the full repertoire of these molecules and their respective modifications remain undefined. Here, we report the discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Treating HEK293T cells with 1 mM propachlor for 30 min decreased the GAPDH activity by 25% (Figure A). GAPDH inhibition is associated with the accumulation of its substrate glyceraldehyde-3-phosphate, which can convert to reactive species that alkylate KEAP1 to induce the oxidative stress response . Indeed, we see that KEAP1 is significantly destabilized by propachlor exposure by the Hsp40 affinity assay (FC = 1.3, p = 0.019, q = 0.02) (Table S4).…”
Section: Resultsmentioning
confidence: 93%
“…Treating HEK293T cells with 1 mM propachlor for 30 min decreased the GAPDH activity by 25% (Figure A). GAPDH inhibition is associated with the accumulation of its substrate glyceraldehyde-3-phosphate, which can convert to reactive species that alkylate KEAP1 to induce the oxidative stress response . Indeed, we see that KEAP1 is significantly destabilized by propachlor exposure by the Hsp40 affinity assay (FC = 1.3, p = 0.019, q = 0.02) (Table S4).…”
Section: Resultsmentioning
confidence: 93%
“…Methylglyoxal is highly reactive and could non‐enzymatically cross‐link and dimerize Keap1 molecules via a methyl imidazole‐based linkage between cysteine (C151) and arginine (R15 or R135) residues, facilitating Nrf2 signaling 72 . More recently, it has been shown that accumulation of glyceraldehyde 3‐p elicits S‐lactoylation of several cysteines in Keap1 by mechanisms that have yet to be elucidated 73 . Since glyceraldehyde 3‐p readily accumulates during sprint exercise, 13 it could contribute to Nrf2 signaling by impeding the inhibitory action of Keap1 through its S‐lactoylation.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,24,71 Keap1 cysteines may be covalently modified by several endogenous metabolites. 62,63,72,73 For example, by methylglyoxal, an electrophile that results from the elimination of triose phosphate, which accumulates in conditions with high glycolytic flux, as occurs during sprint in normoxia 13,71 and sprint 15 or moderateintensity exercise in hypoxia. 74 Methylglyoxal is highly reactive and could non-enzymatically cross-link and dimerize Keap1 molecules via a methyl imidazole-based linkage between cysteine (C151) and arginine (R15 or R135) residues, facilitating Nrf2 signaling.…”
Section: T a B L Ementioning
confidence: 99%
“…Interestingly, KEAP1 can also be modified at cysteine residues by fumarate and glyceraldehyde 3-phosphate ( 57 , 58 ), and by succinylation at a critical lysine sensor residue, also leading to increases in Nrf2 protein levels ( 59 ). Hence, it appears that these PTMs of KEAP1 serve as a generic switch to induce a regulatory stress response to different reactive metabolites ( 59 ).…”
Section: Impact Of Itaconate On Cell Signaling and Metabolismmentioning
confidence: 99%